Rancang Bangun Alat Bantu Pemeriksaan Radiologi pada Pemeriksaan Patella Metode Hughston - Mufida, Widya; Faesol, Ahmad (Poltekkes Kemenkes Semarang, 2024)
Background: Radiographic examination of the tangential projection of the patella can be done in a prone, supine body position, sitting on an examination table with legs dangling, or standing with a different angle for each method. The Hughston method is carried out with an angle of 55 degrees. Hughston's method of radiographic examination of patients is holding a frozen strap to the leg in order to obtain the desired angle so that if the patient's condition is non-cooperative, attack the radiographer to carry out the examination optimally. The purpose of this study was to make a Patella radiological examination tool using the Hughston method.Methods: This research is an experimental research by making inspection aids first followed by testing on anthropomorphic phantoms and volunteers. The results obtained are then analyzed to get conclusions and suggestions.Results: In the design of the Patella radiographic examination fixation device, the Hughston material method is used as needed and does not interfere with the image such as artifacts in the image. The specifications of the fixation device for patella radiographic examination by the Hughston method are made of acrylic which has properties that can be penetrated by radiation without causing artifacts, the height of the fixation device is 25 cm with a slope angle of 55 degrees, length 26 cm and width 20 cm. The angle of the fixation device is intended so that the supporting position of the patient's leg is extended with an angle of 55 degrees cephalad. The results of the radiograph are expected to evaluate the wear on the patellofemoral joint surface, identify the lateral half of the patella and determine the correlation between the femur and tibia. The prone position of the patient in the Hughston method cannot be used in patients with clinical fractures or patella dislocations.Conclusions: The fixation device that has been made is in accordance with the expected projection on the Hugstons projection patella radiographic examination. Trials using this fixation device use volunteers to make it easier to adjust the patient's actual position without exposure. The reason for not using a phantom is because the position of the phantom pedis is stiff so that it covers the irradiation and causes superposition